Sleep Management within Skilled Nursing Facilities: A Practice Survey. Issue 1 (3rd January 2023) - Enam, Nabila; Grampurohit, Namrata; Farber, Ruth S.
Abstract: A cross-sectional descriptive survey of 105 occupational therapy practitioners examined the practice patterns in sleep management within skilled nursing facilities. All participants viewed sleep as essential to address in their settings, since clients frequently reported inadequate sleep, daytime sleepiness, difficulty staying asleep, and situational interruption. Majority of the practitioners reported not screening, assessing, treating, or documenting sleep issues and lack the use of standardized assessments and evidence-based interventions for sleep. Results suggest that practitioners need more training, education, and advocacy skills to promote the role of occupational therapy in addressing sleep management in skilled nursing facilities.